CERDAS FINANSIAL DAN PENGUATAN “MINDSET YOUNGPRENEURSHIP” PADA IKATAN PELAJAR MUHAMMADIYAH (IPM) SIDAYU GRESIK - Ismanto, Hadi; Aufa, Muhammad (Universitas Muhammadiyah Gresik, 2023)
University Muhammadiyah Gresik through the entrepreneurship study program and the accounting study program collaborated with the Muhammadiyah Sidayu Student Association. This collaboration resulted in program synergy in the form of financial smart seminars and strengthening the “Youngpreneurship Mindset”. The result of this service activity is o build financial intelligence in IPM Sidayu cadres so they are able to manage finances effectively and efficiently. Financial intelligence is expected to encourage changes in the consumer mindset to become an entrepreneur mindset.